Gambaran psychological well being pada pasien gagal ginjal kronik yang menjalani terapi Hemodialisa - Nurhaeda, Nurhaeda (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Abstract: Psychological well-being is not only the absence of psychological pressure or problems but also the state of accepting oneself and one's past, experiencing personal growth, finding meaning and purpose in life, maintaining positive relationships with others, effectively managing one's life and environment, and having the ability to make autonomous decisions. Hemodialysis therapy has an impact on the physical, psychological, and social well-being of patients, specifically on the psychological well-being of individuals with chronic renal failure. The objective of this study is to examine the psychological well-being of patients undergoing hemodialysis therapy for chronic renal failure. The research employed a qualitative method with a phenomenological study approach. Data were collected through interviews and observations involving three participants. The purposive sampling technique was utilized, and the collected data were analyzed thematically. The findings indicate that individuals with chronic renal failure who undergo hemodialysis therapy initially go through a phase of rejecting their condition. They may experience emotions such as anger, fear, despair, and anxiety. However, these emotions tend to diminish with the support received from their families and the social environment. Besides family and social support, other factors contribute to the improvement of their psychological well-being. These factors include economic stability and a sense of fulfillment in fulfilling parental responsibilities. This state of mind leads to a sense of tranquility and motivates patients to adhere to medical recommendations, ultimately influencing their overall quality of life.Keywords: chronic renal failure; hemodialysis; psychological well being